Association between neurofibromatosis type 1 and piebaldism confirmed by genetic analysis. Review of the literature. - Aranibar Durán, L.; Guzmán Rossi, A.; Burckhardt-Bravo, V. (European Journal of Pediatric Dermatology, 2025)
Other cases fulfilling the diagnostic criteria for NF1 and piebaldism have been described in the literature, suggesting a possible association between these conditions. However, this relationship remains uncertain. To our knowledge, the current case is the first to document the association between neurofibromatosis type 1 and piebaldism, confirmed by genetic analysis, and to underline the importance of genetic studies in the early diagnosis of these conditions.